Maximal and sub-maximal power generation capacity and physiological responses in Japanese internationally competitive speed skaters - Kumagawa, D.; Akiyama, K.; Imawaka, T.; Arimitsu, T. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: The force and power generation capacities of the lower limb muscles are improved by speed skating training in speed skaters (Nemoto et al. 1990, de Koning et al. 1991). There are differences in aerobic and anaerobic power output between short-distance and middle- to long-distance skating (de Koning et al. 2005). On the other hand, there is little knowledge about the age-related differences in such physical fitness characteristics in speed skaters. Especially, there is very little knowledge about the difference between senior athletes and junior skaters regarding maximal and sub-maximal power generation capacity among top athletes. This study therefore evaluated the maximal and sub-maximal power generation capacity and physiological responses of senior and junior Japanese internationally competitive speed skaters.